Intra-oral Mucosal Conditions In A Group of Edentulous Patients - Sartawi , Samiha; Hassonah, Yazan; Alqaisi , Duaa; Salim , Nesreen; Alomoush, Salah (Jordan Medical Journal, 2025)
Objectives: To obtain baseline information on Oral Mucosal Conditions (OMCs) in a sample of patients who are edentulous. Materials and methods: Edentulous patients attending a university hospital were examined for the presence of OMCs, and demographic data were recorded. Statistical analysis was carried out on SPSS software; the following statistical tests were utilized: descriptive statistics, and The Mann Whitney U test. Results: A total of one hundred and sixty-one participants were examined (34 females and 127 males with a mean age of 59 years). Sublingual varices were the most common OMC (54.7%) followed by hairy tongue (48.4%), fissured tongue (44.7%), leukodema (41.6%), Fordyce’s Granules (30.4%), Smoker palate (23.6%), Frictional Keratosis (14.9%) and Geographic Tongue (3.64%). Among denture wearers denture stomatitis (6.2%) was the most common, followed by denture Fissurratum (3.7%) and angular chelitis (3.7%). Smoking was associated with higher prevalence of OMCs, particularly hairy tongue, frictional keratosis, smokers’ palate, and leukoedema. Denture wearers had more denture stomatitis and denture induced hyperplasia, and less frictional keratosis than non-denture wearers. Conclusion: Mucosal changes in edentulous patients are affected by smoking, medical conditions, and superimposed by wearing complete dentures.